The lifeboat problem - Kai A. Konrad; Dan Kovenock (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2011)
We study an all-pay contest with multiple identical prizes (lifeboat seats). Prizes are partitioned into subsets of prizes (lifeboats). Players play a two-stage game. First, each player chooses an element of the partition (a lifeboat). Then each player competes for a prize in the subset chosen (a seat). We characterize and compare the subgame perfect equilibria in which all players employ pure strategies or all players play identical mixed strategies in the first stage. We find that the partitioning of prizes allows for coordination failure among players when they play nondegenerate mixed strategies and this can shelter rents and reduce rent dissipation compared to some of the less efficient pure strategy equilibria.
Keywords: D72; D74; 330; All-pay contest; multiple prizes; rent dissipation; lifeboat